Specialità e specificità umana e animale: il caso dell’altruismo - Consuelo Luverà (Rivista Italiana di Filosofia del Linguaggio)
According to some theories human beings’ moral capacity is discontinuous with the natural capacities of all nonhuman species. They are basically bad and selfish: their good behavior must be explained as an artificial product of the cultural human properties: this conception views morality as a cultural innovation achieved by our species alone. By contrast other theories hold that humans are by nature altruist: good nature is inherited from our nonhuman ancestors. According to this conception human moral behavior is continuous with nonhuman behavior. It has its evolutionary origins in emotions that we share with other animals, and it’s a direct outgrowth of the social instincts that we share with other animals, too. When in seventies Edward O. Wilson’s Sociobiology came out perspectives in favor of moral discontinuity between human beings and nonhuman species got a scientific support. Ethological model about altruism elaborated to explain animal behaviors dropped hints that also human altruism was basically a hidden opportunism. However any discussion about altruism must include the caveat that dissimilar socio-ecological conditions will lead to important differences in the altruistic behavior. We need to consider species-specific and eco-ethological properties of each species and the role of language with relation to human cognition in order to comprehend the possibility of altruistic behavior.